Cost-Effectiveness analysis of ultrasound scans during pregnancy in Iran - Sima Ahmadpoor; Hamidreza Farrokh-Eslamlou; Hasan Yusefzadeh; Cyrus Alinia (Health Science Monitor)
Background & Aims: There is limited evidence in Iran regarding the costs, effectiveness, and cost-effectiveness ratios of ultrasound screening scenarios. The aim of this study was to address these knowledge gaps Materials & Methods: We used the cost-effectiveness analysis of one-time pregnancy ultrasound screening (OTPUS) and two-time pregnancy ultrasound screening (TTPUS) strategies from the societal perspective. We applied a Monte Carlo Simulation model including 1000 pregnant mothers and calculated each scenario's cost, effectiveness, and cost-effectiveness ratios based on 2020 data. We took the direct medical (obstetrician’s visits, ultrasound tariffs, and confirmatory tests) and non-medical costs (travel costs) into account to calculate the costs based on the bottom-up approach. Moreover, we estimated the number of detected fetal anomalies as an effectiveness factor by considering the sensitivity and specificity of the screening methods. The average and incremental cost-effectiveness ratios determine the cost-effectiveness of each screening scenario. The data on costs were extracted from the official Iranian public sector tariffs in 2020. Moreover, the epidemiological and diagnostic accuracy data were extracted from the published evidence. We applied the one-way sensitivity analysis to determine the effects of data uncertainty on the study's findings. Results: The screening costs per pregnant mother in the OTPUS and TTPUS models were $12.08 and $17.35, and the effectiveness of these approaches was 8 and 17 detected fetal anomalies per 1000 pregnant mothers, respectively. The average cost-effectiveness ratios were $1509.50 for OTPUS and $1020.35 for TTPUS. Finally, the cost of diagnosing an additional anomaly in the two-time ultrasound approach was $585.56. Conclusion: The OTPUS model imposes 43.6% lower costs on pregnant mothers, but also detects a significantly lower number of fetal anomalies. TTPUS policy needs $585.56 more to find an extra case.